Combining linkage and association mapping approaches to study the genetic architecture of verticillium wilt resistance in sunflower - Montecchia, Juan Francisco; Fass, Monica Irinia; Dominguez, Matías; Gonzalez, Sergio Alberto; Garcia, Martin Nahuel; Filippi, Carla Valeria; Ben Guerrero, Emiliano; Maringolo, Carla Andrea; Troglia, Carolina Beatriz; Quiroz, Facundo Jose; Gonzalez, Julio Horacio; Alvarez, Daniel; et al. (MDPI, 2025)
Sunflower Verticillium Wilt and Leaf Mottle (SVW), caused by Verticillium dahliae Kleb., is a globally prevalent disease affecting sunflower production. In this study, we identified a major quantitative trait locus (QTL) on chromosome 10 and other genomic regions associated with SVW resistance by integrating biparental and association mapping in sunflower populations from the National Institute of Agricultural Technology. Nine replicated field trials were conducted in highly infested V. dahliae reservoirs to assess disease incidence and severity. Both mapping populations were genotyped using double-digest restriction-site-associated DNA sequencing (ddRADseq). Association mapping with 18,161 SNPs and biparental QTL mapping with 1769 SNPs identified a major QTL on chromosome 10 explaining up to 30% of phenotypic variation for disease incidence at flowering and for the area under the disease progress curve for disease incidence, and which contributes to a lesser extent to disease severity reduction. Additional QTLs on chromosomes 17, 8, 9, 14, 13, and 11 were associated with reduced disease incidence, severity, or both. Candidate genes were identified within these associated regions, 39 of which are in the major QTL on Chromosome 10. These findings demonstrate the value of integrating complementary QTL mapping strategies for validating resistance loci and advancing sunflower breeding for SVW resistance.